2020
DOI: 10.1186/s13058-020-01279-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the adolescent female breast transcriptome and the impact of obesity

Abstract: Background: Early life environmental exposures affect breast development and breast cancer risk in adulthood. The breast is particularly vulnerable during puberty when mammary epithelial cells proliferate exponentially. In overweight/obese (OB) women, inflammation increases breast aromatase expression and estrogen synthesis and promotes estrogen-receptor (ER)-positive breast cancer. In contrast, recent epidemiological studies suggest that obesity during childhood decreases future breast cancer risk. Studies on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 75 publications
0
7
0
1
Order By: Relevance
“…Similar to the studies of inflammatory blood biomarkers and breast cancer risk, there is currently a complete absence of information on the effect of inflammation during key windows of susceptibility on breast cancer risk, even though we know that the pregnancy/lactation cycle induces an inflammatory state akin to wound healing and that breasts also change in form and function around the menopausal transition, a time in life when subgroups of women also experience weight gain and increases in other chronic disease risk factors [10]. Further, in a recent study evaluating transcriptomic pathways differentially expressed in breast tissue samples from overweight/obese (OB) vs. normal weight adolescents, analyses identified inflammatory genes (cytokines CSF1 and IL-10, chemokine receptor CCR2) as among the most highly activated upstream regulators in the OB breast [52]. This suggests that there are innate inflammatory responses within the OB breast even in early life, again supporting a need to study windows of susceptibility.…”
Section: Medical Conditions Related To Chronic Inflammation and Breasmentioning
confidence: 99%
“…Similar to the studies of inflammatory blood biomarkers and breast cancer risk, there is currently a complete absence of information on the effect of inflammation during key windows of susceptibility on breast cancer risk, even though we know that the pregnancy/lactation cycle induces an inflammatory state akin to wound healing and that breasts also change in form and function around the menopausal transition, a time in life when subgroups of women also experience weight gain and increases in other chronic disease risk factors [10]. Further, in a recent study evaluating transcriptomic pathways differentially expressed in breast tissue samples from overweight/obese (OB) vs. normal weight adolescents, analyses identified inflammatory genes (cytokines CSF1 and IL-10, chemokine receptor CCR2) as among the most highly activated upstream regulators in the OB breast [52]. This suggests that there are innate inflammatory responses within the OB breast even in early life, again supporting a need to study windows of susceptibility.…”
Section: Medical Conditions Related To Chronic Inflammation and Breasmentioning
confidence: 99%
“…17 Some have postulated that adipose tissue itself may contribute significantly to breast size, but our institution’s analysis of reduction mammaplasty specimens, specifically glandular tissue, does not support this theory. 18 RNA sequencing data from these specimens has demonstrated inflammatory transcriptional changes among obese adolescents that may potentiate estrogen action in the immature breast microenvironment. 18 Moreover, our macromastia severity value calculation normalizes breast resection mass to body surface area, and therefore minimizes the likelihood of large body habitus confounding our assessment of hypertrophy severity.…”
Section: Discussionmentioning
confidence: 99%
“…18 RNA sequencing data from these specimens has demonstrated inflammatory transcriptional changes among obese adolescents that may potentiate estrogen action in the immature breast microenvironment. 18 Moreover, our macromastia severity value calculation normalizes breast resection mass to body surface area, and therefore minimizes the likelihood of large body habitus confounding our assessment of hypertrophy severity. 11 The role of adipose tissue as an important endocrine organ cannot be discounted.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, we observed 65 shared DEGs showing the same-direction change in the abdominal WAT of obese monkeys with the results from the Lee et al study 5 . For the Burkholder et al study using breast tissue 12 , we identified 15 overlapping same-direction DEGs in the abdominal WAT. No overlapping DEGs with same-direction changes were detected in the results from other studies.…”
Section: Comparison Of Obesity-associated Transcriptional Changes Between Humans and Cynomolgus Monkeysmentioning
confidence: 99%
“…However, the molecular mechanisms of how these loci regulate gene expression and impact protein function remain poorly understood. Previous studies have investigated the transcriptomes or proteomes of obese patients in tissues including blood 3,4 , adipose tissues [5][6][7][8] , liver 9 , muscle 8,10,11 , breast 12 , granulosa cells 13 , and sperm 14 . However, these studies have yielded inconclusive and sometimes conflicting results about obesity-related molecular changes 15 .…”
Section: Introductionmentioning
confidence: 99%